Implementing Project-Based Learning Using Short Movies in English Writing Course: English - Euis Meinawati; Widia Yunita (Prodi Tadris Bahasa Inggris, 2024)
This research aims to determine the effectiveness of implementing project-based learning using short movie-making in English writing classes. This research uses quasi-experimental research with a one-group pre-test and post-test experimental design. The research was conducted in 14 meetings with 50 English writing class 31.3A students. The odd semester was 2023-2024. The research will be carried out from September 2023 to 2024 at BSI University Jakarta. Data is collected using observation, documentation and tests. The data analysis technique uses a two-sample paired t-test for the mean. The research results concluded that short movie-making projects carried out in groups can increase student interest in writing classes. Apart from that, it is also easier for students to develop writing ideas. So, students' English writing skills are better than before the short movie-making project was implemented. This can be seen from the t-test results showing t-Stat < t-table (5.4678 < 2.0095), meaning that the project of making short movies in groups is practical and improves English writing skills.